Co dalej z Europą Środkową? Miejsce Austro-Węgier wśród brytyjskich celów wojennych w latach 1914-1918 - Jeziorny, Dariusz (Acta Universitatis Lodziensis. Folia Historica, 2003)
On 12th August 1914 His Majesty Government in London declared the war against the Habsburg Monarchy. There was no serious political, strategical and economic interest of Great Britain in Central Europe before World War I. And that is why Great Britain and Austria- Hungary had no serious conflict in history of their bilateral relations. It appeared to be very clear, when Herbert Asquith (British Prime Minister) was announcing British war aims in August-September 1914 and no statesment touched the Francis Joseph’s Empire. Nevertheless the main German ally and the biggest colonial empire began struggle. First preparations towards establishing new order in post-war Europe took place in London in late 1916. Some politicians took up also problems of Central European future Two main points of view appeared during the long discussion. The first camp wanted the Dual Monarchy to be saved. There were different reasons of such a position of the so called “Austrophils” . Lord Robert Cecil (Assistant Secretary in FO), general Johannes Smuts (member of the Cabinet and of the Imperial War Cabinet) and even the Prime Minister David Lloyd George wanted to maintain Austria-Hungary as an important factor of the European ballance of power. Lord Alfred Milner (very influetial member of the War Cabinet and the Secretary of War Office since April 1918) and his supporters prefered to repeat Austro-Hungarian patterns in reconstruction of the British colonial empire. The British Catholics (many served in FO and Diplomatic Service) were helping the Habsburg Monarchy regarded as a Catholic and conservative power. The London City (national and family connections of London and Vienna banks were very often) were afraid of financial destabilisation after breakup of Austria-Hungary. Finally radical circles of Independent Labour Party declared their “hands off” Austria-Hungary because they argued against nationalism, which could appear in the “balkanised” Central Europe. The second group (so called “Austrophobes”) were led by two very powerful persons professor Robert W. Seton-Watson (editor of “The New Europe", founder of The School of Slavonic and East European Studies) and Henry W. Steed (foreign editor of “The Times”) They both claimed right of self-determination for Central European Slavonic nationalities They had their loyal supporters in some very effective and influential governmental departments f.i. in Department of Information Intelligence Bureau, transformed in March 1918 into Foreign Office as Political Intelligence Department and Enemy Propaganda Department. His Majesty Government took no final decision about the future of Austria-Hungary. As far as Central Europe was concerned, the leading idea of British diplomacy was not to interfere politically or military in that region which was regarded as a very dangerous and unstable one. Such “wait and see” policy led to breakup of the Habsburg Monarchy and to final destabilisation of the whole region, which lasted during the interwar period.